HUBUNGAN ANTARA MOTIVASI INTRINSIK DENGAN PRESTASI BELAJAR SISWA KELAS X PADA SMK NURUL IMAN JAKARTA - Gantrivita Nur Ramida; Umi Widyastuti; Darma Rika Swaramarinda (Faculty of Economics, State University of Jakarta., 2014)
The research purpose is to accurate, valid, and reliable data concerning whether there is correlation between intrinsic motivation and year 10 th student’s learning achievement at Nurul Iman Vocational High School Jakarta. The study was conducted for three months from April to June 2014. The method adopted in the study is a survey method with a correlational approach. The population in the study is all year 10 th students at Nurul Iman Vocational High School Jakarta, counted 122 students in total, and the feasible population of the study is year 10 th students majoring in office and administration, counted 72 students. The sample used in the study is 62 students with proportionally random technique. The instrument used in obtaining data for variable X (internal motivation) was in the form of questionnaire with Likert Scale. For variable Y (learning achievement) the data were collected from students’ grades on school report card in the second semester of 2013/2014, issued by Nurul Iman Vocational High School Jakarta. The data analysis technique was done by figuring out the regression equation and the equation is Ŷ = 70.14 + 0.06X. The regression linearity test yielded F counting (1.37) < F table (1.84) therefore it can be concluded that the equation is linear. The correlation coefficient test of product moment yielded r counting = 0.286. The result of the study concludes that there is positive correlation between intrinsic motivation and learning achievement of year 10 th students in Nurul Iman High Vocational School. The test of determination coefficient yielded 8.17% therefore it can be concluded that there is positive and significant correlation between intrinsic motivation and learning achievement.